Formulasi dan Evaluasi Parfum Aroma Dasar dari Minyak Atsiri Daun Aromatik Indonesia dengan Fiksatif Melati - Luthfiah Luthfiah; Tasir Tasir; Rahmawati Saleh (Lembaga Pengembangan Kinerja Dosen, 2025)
The growing demand for natural, sustainable personal care products has driven interest in perfumes formulated with plant-based essential oils and natural fixatives. This study aims to develop and evaluate base-note perfumes using essential oils extracted from three Indonesian aromatic leaves—lemongrass (Cymbopogon citratus), basil (Ocimum basilicum), and kaffir lime (Citrus hystrix)—combined with jasmine (Jasminum sambac) oil as a fixative. Essential oils were extracted by hydrodistillation, and three formulations were prepared, each containing a 30:70 blend of essential oil to ethanol. The perfumes underwent organoleptic testing by 15 trained panelists, along with evaluations of fragrance longevity (over 12 hours) and stain effects on paper substrates. Among the formulations, the blend of kaffir lime and jasmine (Formula 2) exhibited the highest average scores across sensory parameters, including fragrance intensity and freshness. It also retained a perceptible aroma for more than 12 hours and showed minimal staining. The results indicate that natural perfumes made with local essential oils and jasmine fixatives can meet consumer expectations for quality and performance. This study highlights the potential of Indonesian aromatic plants in sustainable perfumery and suggests avenues for future innovation in natural fragrance design.